Two-step chemical mutagen treatment to convert Fuhua 12, a normal oleic Spanish peanut cultivar, into its high oleic version. (October 2019) - Yu, S T; Wang, C T; Wang, H; Yu, G Q; Shi, P X; Ren, L; Yu, H B; Du, Z B
Abstract: High oleic peanut food products have proved to have better keeping quality and several health benefits. Most of the high oleic acid peanut cultivars thus far released were bred through hybridization. Breeding through mutagenesis directly provides a possibility of keeping the main agronomic characteristics from the parental cultivars/lines unchanged in the new cultivars, which is of significance to their use in commercial production. The aim of the present study was to convert Fuhua 12, a normal oleic Spanish peanut cultivar, into a high oleic version through EMS (ethyl methane sulfonate) mutagenesis. The effect of the first round of EMS treatment of Fuhua 12 on oleic acid content was limited. However, after the second round of EMS treatment, we were able to identity a high oleic plant through near infrared spectroscopy (NIRS) and further studies by gas chromatography and sequence comparison of the mutated type and wild type FAD2A/FAD2B genes. The mutant had the same mutations in FAD2A and FAD2B as UF435. A G448A substitution in FAD2A and an A insertion (441_442insA) in FAD2B together contribute to the high oleic phenotype of the mutant. In this study, Fuhua 12 was successfully converted into a high oleic version without changing most of the agronomic characters, demonstrating the utility of a two-step chemical mutagen treatment protocol in inducing useful mutations in the cultivated peanut. The novel method may expedite genetics and breeding studies in the cultivated peanut, and is of reference to other polyploid plant species.